Food, fermentation, and micro-organisms - Bamforth, Charles W. (Blackwell Science, 2019)
Contents of the book is guide for all food scientists, technologists and microbiologists in the food industry and academia, this book will be an important addition to all libraries in food companies, research establishments and universities where food studies, food science, food technology and microbiology are studied and taught